Naviguer les attentes genrées de la communauté de danse swing de Montréal - Batty, Megan (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Gender and Extreme Metal: Understanding Gender Relations in the Montreal Extreme Metal Scene With Schippers' Gender Framework - Beauchamp, Caroline (Université Concordia, 2021)
Extreme metal is a masculine space, yet more and more women join in. They face a contradiction: as women, they are expected to adopt feminine behaviours; however, they are part of a subculture that valorizes warrior masculinity. I sought to understand the gender expectations of the Montreal extreme metal scene and interpret the contradictions encountered by women in this scene with the help of Schippers’ (2007) theoretical framework on gender. To do so, I conducted 16 individual interviews with women and men who take part in the scene. This research fills a gap in the literature on gender that derives from Connell and Schippers’ writings and addresses issues that the field of metal studies has brushed over. I found that metal men are the “default” participants in the scene. They are expected to be fine music connoisseurs and even become musicians. In contrast, women’s presence is heterosexualized and attributed to a romantic or sexual interest in metal men. Women are suspected of being “poseuses” or groupies with no real interest in the music until proven otherwise. To become legitimate participants, they have to overcome those expectations and prove that they are worthy of being viewed through the prism of masculinity rather than femininity. They do so by proving their exceptionality through manhood acts and distancing themselves from other women. Despite their gender transgressions, women’s presence does not fundamentally question gender relations but reaffirms the overall primacy of masculinity over femininity.

Énonciation, sexualités et genre en musique chez Philémon Cimon, Pierre Lapointe et Ariane Moffatt - Konaté, Khady (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Dans ce texte est proposée une « lecture du genre » (Boisclair 2002) des oeuvres de Philémon Cimon (L’été, Les femmes comme des montagnes), Pierre Lapointe (Pierre Lapointe, Sentiments humains) et Ariane Moffatt (Aquanaute, Le coeur dans la tête, Tous les sens). L’étude des chansons contenues sur ces albums prend pour point de départ une interrogation des subjectivités genrées de ces trois artistes, entre personne réelle et persona, et montre que ces dernières façonnent leurs compositions. La sollicitation du concept de sexe/genre ouvre dès lors la porte à l’exploration des représentations des identités sexuelles et de genre dans ces chansons, où les identités des artistes se trouvent mises en abîme. En s’intéressant à l’énonciation et au discours (en particulier, au discours amoureux) contenu dans le texte des chansons sélectionnées, il est possible de rendre compte de la reproduction des injonctions à l’hétérosexualité et des poncifs qui cloisonnent le genre, ainsi que des glissements et brouillages qui autorisent des resignifications du genre. Ainsi, chez Cimon, on observe la reconduite du point de vue masculin où la valeur du féminin réside dans sa capacité à émerveiller le sujet et à susciter son désir. À l’opposé, les textes de Lapointe et Moffatt dépeignent des personnages et des récits queer, bien que leur identité queer n’ait pas été revendiquée à l’heure de la parution de leurs oeuvres.

Genre, rap et enjeux de la visibilité dans l'espace public des rappeuses à Montréal : de la gestion de l'apparence physique pour être reconnue en tant qu'artiste - Lesacher, Claire (Les Cahiers de la Société québécoise de recherche en musique, 2021)

The Double Bind That Is Not a Bond: Cohen and Women - Pally, Marcia (From This Broken Hill I Sing to You: God, Sex, and Politics in the Work of Leonard Cohen, 2021)
Leonard Cohen's troubled relationship with God is here mapped onto his troubled relationships with sex and politics. Analysing Covenantal theology and its place in Cohen's work, this book is the first to trace a consistent theology across sixty years of Cohen's writing, drawing on his Jewish heritage and its expression in his lyrics and poems.Cohen's commitment to covenant, and his anger at this God who made us so prone to failing it, undergird the faith, frustration, and sardonic taunting of Cohen's work. Both his faith and ire are traced through: · Cohen's unorthodox use of Jewish and Christian imagery · His writings about women, politics, and the Holocaust · His final theology, You Want It Darker, released three weeks before his death.
Keywords: Music / General; Religion / Judaism / Theology; Religion / Theology